Synthesis, Liquid Crystal Characterization and Photo-Switching Studies on Fluorine Substituted Azobenzene based Esters - Mei, Gan Siew; A. R., Yuvaraj; Lutfor, M. R.; M. M., Yusoff; Hegde, Gurumurthy (Royal Society of Chemistry, 2015)
A series offluorinated azobenzene esters have been synthesized and studied by polarized optical microscopy (POM) and UV-Vis spectrophotometry. The–CO2C2H5group with monofluoro-substituted azobenzene exhibited nematic and smectic phases whereas difluoro-substituted azobenzene showed only the nematic phase. The addition of the electronegativefluorine atom plays an important role in photoisomerization of the azobenzene molecules. The monofluoro-substituted azobenzene gave strong photoisomerization in solution as compared with its diflouro counterparts. In these systems,trans–cis isomerization occurred after 4 minutes and cis–trans isomerization occurred after 22 hours which is much longer than expected forfluorine-substituted azobenzene systems. The presented results might have an influence on creating optical data storage devices.